english Antimicrobial properties of lysozyme in meat and meat products: possibilities and challenges - Zahra Pilevar; Khadijeh Abhari; Hasan Tahmasebi; Samira Beikzadeh; Roya Afshari; Soheil Eskandari; Mohammad Jafar Ahmadi Bozorg; Hedayat Hosseini (Acta Scientiarum. Animal Sciences, 2022)
Meat and meat products are highly perishable as they can provide an appropriate environment for microbial growth due to their high water activity and proper pH level. Quality, safety, sensory and nutritional properties of meat products are highly influenced by pathogenic and spoilage microorganisms. To prevent microbial growth, artificial antimicrobials have been used in food matrices, however safety concerns regarding the use of synthetic preservatives is a challenging issue. Additionally, consumer’s trend towards natural mildly processed products with extended shelf life necessitates the identification of alternative additives originating from natural sources of new acceptable and effective antimicrobials. Although the effectiveness of some natural antimicrobial agents has already been reported, still, there is lack of information regarding the possibility of using lysozyme as a preservative in meat and meat products either alone or in combination with other hurdles. In the present review the applications and beneficial effects of applying lysozyme in meat products, considering its limitations such as allergic problems, interactions with food constituents, reducing sensory changes and toxicity due to high required concentrations to prevent spoilage and oxidation in foods will be discussed